Action cameras and the Roter interaction analysis system to assess veterinarian‐producer interactions in a dairy setting. (24th February 2018) - Ritter, Caroline; Barkema, Herman W; Adams, Cindy L
Abstract : Herd health and production management (HH&PM) are critical aspects of production animal veterinary practice; therefore, dairy veterinarians need to effectively deliver these services. However, limited research that can inform veterinary education has been conducted to characterise these farm visits. The aim of the present study was to assess the applicability of action cameras (eg, GoPro cameras) worn by veterinarians to provide on‐farm recordings, and the suitability of these recordings for comprehensive communication analyses. Seven veterinarians each recorded three dairy HH&PM visits. Recordings were analysed using the Roter interaction analysis system (RIAS), which has been used to evaluate medical conversations in human and companion animal contexts, and provided insights regarding the importance of effective clinical communication. However, the RIAS has never been used in a production animal environment. Results of this pilot study indicate that on‐farm recordings were suitable for RIAS coding. Dairy practitioners use a substantial amount of talk allocated to relationship‐building and farmer education but that communication patterns of the same veterinarian vary considerably between farm visits. Consecutive studies using this method will provide observational data for research purposes and promise to aid in the improvement of veterinary education through identification of communication priorities and gaps in dairy advisory discussions.